Yabuki's Easy - to - pronounce romanized Japanese wordbook - Yabuki, Katsuji (Japan Travel Bureau, 1980)
This book has about 2700 English main entry words. The Japanese definitions and related phreases for them total nearly 4500. All the English and Japanese words are easy, common ones chosen on the basis of researches made in Japan and abroad.